Incipient Racism? When Does it Start? Racial Attitude Development in Young Children - Katz, Phyllis A. (Advances in Social Sciences Research Journal, 2020)
The present study examined the forerunners of racial attitudes in two groups of children (from Black families and White families). Assessments of various cognitive and perceptual skills were conducted longitudinally at seven age points from six months to three years of age. Racial attitudes were present in almost half of the children by three, although not all had yet exhibited mastery of underlying skills. Both groups of children exhibited similar pro-same race attitudes at 36 months, but some divergence in developmental patterning began at 30 months of age. Some parental behaviors such as parental willingness to discuss race and diversity of the child’s environment were related to attitudes at three.